Standar Pelayanan Keperawatan Pada Penilaian Akreditasi Rumah Sakit Versi 2012 Di Rumah Sakit “X” Tahun 2016 - Ni Nyoman Dwi Sutrisnawati; Dumilah Ayuningtyas (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Hospitals are required to carry out accreditation periodically, at least once every three years. The development of hospital accreditation standards in Indonesia has undergone adjustments in 2016 referring to the 2012 version of accreditation standards which focus on patients. Hospital "X" has been accredited with five basic services in the 2007 version of the accreditation assessment. The aim of this research is to analyze the gap between the existing service standards applied at Hospital "X" and the assessment elements included in the three standards in 2012 version of National Hospital Accreditation related to nursing services. This research uses a case study method with a descriptive analytical design. Data collection was carried out by interviews, observation and document review. This research was conducted in February - April 2016. The research found that the service standards for Patient and Family Rights and Patient and Family Education were still not optimal, there were policies and documents that did not officially exist. Infection Prevention and Control (PPI) service are not yet optimal due to the unsustainable function of the committee and lack of facilities and infrastructure, while the Accreditation team organization has gone quite well, even though with limited members. The fulfillment at Hospital "X" still needs to be improved. It is recommended that the documents and policies be coordinated and socialized immediately, so that they can be implemented. Regular assistance and evaluation by management is still needed to achieve the target.